Dramatyczne konstruowanie twarzy w wybranych utworach Tadeusza Różewicza - Woźniak, Ewelina (Wydawnictwo Naukowe UAM, 2014)
The purpose of this article is to present Tadeusz Różewicz as a poetic portraitist. Faces very often appear in the poet’s works and they play a special role there. The methods that are used to construct them can be grouped into four main categories: 1) a face as a performing subject, 2) a face as an object, 3) a face as a static construct, and finally 4) a face as an element, or metonymy, of human existence and entanglement with reality. In Różewicz’s poetry the human face is material and a mirror, but also a universal symbol of the human condition. These faces are usually distorted, decaying, and blurred. They symbolize the disintegration of the world in which human beings have to live. For Różewicz a face is the most condensed image of humanity and an equivalent of a substance in which every external stimulus leaves its mark. The way of using faces as a material and the process of disintegration that is described in detail constitute a dramatic and performative action which implements the objectives of fluid aesthetics, thus showing the moments of transition from meaning to nothingness and the process of erasing meaning.
Dramatic construction of faces in Tadeusz Różewicz’s selected poems